A new method based on Fiber Bragg grating sensor for the milling force measurement. (October 2015) - Liu, Mingyao; Zhang, Zhijian; Zhou, Zude; Peng, Shuang; Tan, Yuegang
Abstract: Milling force is an important parameter to describe the mechanical processing chip removal process, and it has a direct influence on generation of heat, tool wear or failure, quality of machined surface and accuracy of the work piece. Its accurate measurement is a significant basis for judging process state and improving the reliability of machining system. In this study, through analyzing the variation rule of ring diameter, a new method that using Fiber Bragg grating sensors and variation rule of ring diameter to measure the milling force has been proposed, and the basic structure of annulus has also been designed. A dynamometer has also been constructed, and the preliminary verification test was done. Through the analysis of experimental data, the dynamometer based on annulus elastic body can be used in milling force test, and it owns high sensitivity.